Melestarikan Budaya Jawa Melalui Media Digital: Studi Etnografi Virtual tentang Adaptasi Strategis Radio Puspa FM - Zainal Abidin Achmad; Roziana Febrianita; Heidy Arviani (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
As a station dedicated to preserving local Javanese culture, Puspa FM faces challenges in expanding its audience and increasing advertising revenue within a competitive media landscape. This study examines Radio Puspa FM's strategic adaptation in Pacitan, Indonesia, amid digital transformation and cultural commodification. Using a qualitative approach and virtual ethnography, researchers interacted with the station as listeners, community members, and contributors. Seven informants were purposively selected based on their active involvement in Puspa FM's management, cultural programming, and online listener communities. We triangulated in-depth interviews, participant observation, and a focus group discussion as our data collection methods. The findings reveal that Puspa FM utilizes digital platforms such as Facebook, Instagram, and YouTube to extend its reach and attract advertisers, while participatory engagement sustains its cultural authenticity. It also shows that the station reconfigures its content and business model to enhance engagement and sustainability while maintaining its cultural mission. The study implies that integrating digital innovation with participatory values can serve as a practical model for local cultural media seeking to balance tradition, audience engagement, and financial resilience in the digital era.